Efektivitas Pembelajaran Muatan Lokal Kitab Safinatun Naja Terhadap Praktik Shalat Siswa Di Mts Hubbul Wathan Cilawu Garut - Fauziah, Hapsah; Pakih, Pakih (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
The study of the Safinatun Naja book has become commonplace in non-formal educational institutions and is increasingly integrated into formal institutions, particularly in local content subjects. At MTs Hubbul Wathan, a formal educational institution, Safinatun Naja has been an integral part of the Fiqh curriculum for the past eight years. This research aims to enhance students' understanding of prayer practices, addressing the observed gaps in their comprehension. To evaluate the effectiveness of incorporating the Safinatun Naja book into local content learning and its impact on students' ability to perform prayers at MTs Hubbul Wathan Cilawu, a comprehensive study is necessary. The objectives of this research are to: (1) Describe the implementation of the local content learning of the Safinatun Naja book at MTs Hubbul Wathan Cilawu, (2) Describe the students' competence in practicing prayers at MTs Hubbul Wathan Cilawu, and (3) Describe the effectiveness of integrating the local content learning of the Safinatun Naja book in enhancing students' ability to perform prayers at MTs Hubbul Wathan Cilawu. This research employs a descriptive analytical qualitative method, supported by data collected through field research. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted through data reduction, data display, and conclusion drawing. The findings indicate that the integration of the Safinatun Naja book into local content learning at MTs Hubbul Wathan Cilawu has been effectively implemented. This effectiveness is evidenced by several key factors observed during the teaching and learning process: well-organized material, effective communication between teacher and students, mastery and enthusiasm for the subject matter, positive attitudes towards students, fair assessment practices, and measurable student learning outcomes. Keywords: Effectiveness, Safinatun Naja Book Learning, Students' Prayer Practice Competence